2013
DOI: 10.1089/ars.2012.4867
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Redox Reactions and Red Blood Cell Aging

Abstract: Significance: The physiological mechanism(s) for recognition and removal of red blood cells (RBCs) from circulation after 120 days of its lifespan is not fully understood. Many of the processes thought to be associated with the removal of RBCs involve oxidative stress. We have focused on hemoglobin (Hb) redox reactions, which is the major source of RBC oxidative stress. Recent Advances: The importance of Hb redox reactions have been shown to originate in large parts from the continuous slow autoxidation of Hb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 99 publications
0
116
0
4
Order By: Relevance
“…Our results corroborated with the findings of Ojezele and Abatan (2009), who reported a reduction in RBC and Hb in MD treated group, which can be attributed to intravascular haemolysis, anemia, or to haemopoeisis depression. On the other hand, the Hb is found to be a major source of radical production when it interacts with redox xenobiotics (French et al, 1978;Rifkind and Nagababu, 2013). Liver is the target organ of OPs toxicity (Mazumder, 2005), and the leakage of hepatic enzymes such as ALT, AST and ALP are commonly used as an indirect biochemical index of hepatocellular injury (Klaassen and Watkin, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborated with the findings of Ojezele and Abatan (2009), who reported a reduction in RBC and Hb in MD treated group, which can be attributed to intravascular haemolysis, anemia, or to haemopoeisis depression. On the other hand, the Hb is found to be a major source of radical production when it interacts with redox xenobiotics (French et al, 1978;Rifkind and Nagababu, 2013). Liver is the target organ of OPs toxicity (Mazumder, 2005), and the leakage of hepatic enzymes such as ALT, AST and ALP are commonly used as an indirect biochemical index of hepatocellular injury (Klaassen and Watkin, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Although hemoglobin is best known for its role as an oxygen carrier in erythrocytes, many biological functions of hemoglobin predate the evolution of the circulatory system and are used to modulate various redox functions and interactions with gaseous transmitters such as nitric oxide (NO) and hydrogen sulfide (H 2 S) (1)(2)(3)(4)(5). For instance, clams living in H 2 S-rich waters upregulate intracellular hemoglobin levels as a protective mechanism against H 2 S toxicity (5).…”
Section: Introductionmentioning
confidence: 99%
“…11 Increased accumulation of oxidized and denatured proteins, particularly hemoglobin, is also documented. 12 Studies have shown that erythrocyte aging in vivo is accompanied by a reduction in sodium-potassium adenosine triphosphatase (Na/K-ATPase), 13 Gardos channel, 14 and calcium (Ca 2 + )-ATPase with a concomitant significant increase in intracellular calcium. 15 Additionally, metabolic and functional changes have been observed for young and old erythrocytes kept outside the blood circulation.…”
Section: Introductionmentioning
confidence: 99%